2021
DOI: 10.1098/rspa.2021.0452
|View full text |Cite
|
Sign up to set email alerts
|

On a class of q -orthogonal polynomials and the q -Riemann–Hilbert problem

Abstract: We give an explicit solution of a q -Riemann–Hilbert problem that arises in the theory of orthogonal polynomials, prove that it is unique and deduce several properties. In particular, we describe the asymptotic behaviour of zeros in the limit as the degree of the polynomial approaches infinity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Remark 2.4. It can be shown that solution of the RHP given by definition 2.1 satisfies a Lax pair, namely a q-difference equation in z and a recurrence relation for the parameter n. The proof follows using the same arguments as in [5].…”
Section: Statement Of Rhpmentioning
confidence: 86%
See 1 more Smart Citation
“…Remark 2.4. It can be shown that solution of the RHP given by definition 2.1 satisfies a Lax pair, namely a q-difference equation in z and a recurrence relation for the parameter n. The proof follows using the same arguments as in [5].…”
Section: Statement Of Rhpmentioning
confidence: 86%
“…In this paper, we described the asymptotic behaviour of a class of qF II polynomials, defined in section 1.3, by using the q-RHP setting [5]. Our main results are theorems 1.5, 1.7 and 1.8.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we determined the asymptotic behaviour of a general class of qorthogonal polynomials by using the q-RHP setting [19]. The work is motivated by the methods developed by Deift et al [9], which used the RHP setting to determine the asymptotic behaviour of semi-classical orthogonal polynomials.…”
Section: Discussionmentioning
confidence: 99%
“…Extending on our earlier theory [19], in this paper we will use a RHP to obtain detailed asymptotic results for a large class of q-orthogonal polynomials. We will observe an interesting intersection with q-RHP theory and provide explicit examples highlighting aspects of q-RHP theory discussed in the literature [26,29,1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation